Comparing observed and hypothetical climates as a means of communicating to the public and policymakers: The case of European heatwaves. Issue 67 (January 2017) - Beniston, Martin; Stoffel, Markus; Guillet, Sébastien
Highlights: Heatwaves observed in the past 20–30 years would have been less intense if climate had remained similar to its 1950s levels. Recent warming, partly as a result of anthropogenic activity, largely explains the rapid rise in extreme heatwaves since 2000. A more stable climate of the 1950s would have resulted in far less severe heatwave-related impacts. Comparing differences between observed and stationary climates helps in communicating the urgency of taking climate action. Abstract: The summer of 2015 in many parts of Europe was seen to break record hot temperatures, and was the second-hottest on record after the 2003 event. Here we use de-trended climate data since 1951 to assess the difference in peak temperatures and duration of hot summers had climate not warmed by over 1 °C at the scale of the Northern Hemisphere. The rise in mean European summer temperatures since the 1950s has certainly contributed to the intensity of European heatwaves (e.g., 2003, 2010, or 2015) compared to what they could have been in a more stationary climate. Here we show that the number of hot days in the de-trended record would have been reduced by 10–25% for the 30 °C threshold and by 25–50% for the 35 °C level. As a consequence, the severity of the impacts on natural and managed systems linked to extensive and prolonged heatwaves would have been far more limited. The simple statistical approaches presented in this study, that highlight the reduced intensity of heatwaves in a hypothetical "stationary climate", can serve to raise awareness as to the need to limit future warming and help guide policy, for example in the implementation of the "+1.5 °C policy" recently negotiated at the COP-21 climate conference in Paris.